Integrated business transformation : maximizing value by connecting strategy to key capabilities - Pérez La Rotta, Alberto (Emerald points., 2018)
Drawing upon a model developed over 25 years of experience and successfully taught for many yearsat his company Wilson Learning Andina y Rio de la Plata, Alberto Pérez La Rotta presents a comprehensive and replicable approach to integrated business transformation that synchronizes natural human behavior with the needs of leadership, sales, customers, and teams. Here La Rotta provides a roadmap to his method as well as case studies from across Latin America and across the financial services, chemical, pharmaceutical, industrial equipment, and consumer products industries, and he demonstrates how to clarify the challenges facing an organization, define a new value proposition, and connect strategy to key capabilities rooted in an organizations leadership, culture, sales potential, customer focus, and a value chain. This allows organizations to develop and implement solutions that generate transformation and growth and measure the impact of the transformation on the organization and systems. La Rotta clearly connects theory to practice in each of its real-world business cases, making "Integrated Business Transformation" of interest to researches, students, and practitioners.